Reality of having bed nets at home, their status and pattern of using it at night among the population of Lakhantari Village Development Committee of Nepal - Thapa, Bijay Kumar; Pokharel, Kapil Kumar; Chaurasia, Nitendra; Acharya, Alok; Mishra, Rimu; Sharma, Ganesh (Journal of College of Medical Sciences-Nepal, 2018)
Background & Objectives: The use of insecticide treated nets has been advocated for the prevention of the vector borne transmitted disease (malaria) by the World Health Organization and UNICEF for more than a decade. In spite of this, there is no significant reduction in the transmission of the disease. Main objectives of study were to find out the real pattern of using it, to find out the physical integrity of the bed nets being used, and to prove the correlation in between the physical integrity of bed nets and the disease outcome. Torn bed nets with holes size more than 1.2 mm were considered as “holes” in this study. Materials & Methods: A community based cross- sectional study was carried out in Lakhantari VDC within the duration of two weeks. This VDC has been named recently as Gramthan Gaupalika one of State one. Sample size of 384 was determined by the WHO sample size calculator. Face to face interview technique was used after taking consent from individual. Confidentiality was maintained. It was ethically approved by the IRC (Institutional Review Committee) of Nobel Medical College. Results: A total of 384 household were studied. Total household had bed nets but the physical integrity of bed nets was not intact. Almost 73% of the bed nets were torn having more than four holes in them. Nearly 94% of household used bed nets only for three to four days a week. Nearly half of the Malaria was found among 22% and encephalitis in 17% of household. Conclusion: Use of bed nets do not prevent and provide guarantee from vector borne disease unless it is properly used. Torn bed nets are of almost no use unless people are using other preventive measures.